The Exercise of Rights of Internally Displaced Persons in Ukraine - Anastasiia Trofymenko (Історико-політичні проблеми сучасного світу, 2017)
The weaknesses of the legal framework of social protection of internally displaced persons (IDPs) in Ukraine have been analyzed. Among them are legal conflicts between legal acts, absence of the mechanism of providing IDPs with free temporary housing and compensation for lodging destroyed. The following challenges arise under the exercise of rights of IDPs: the amount of targeted aid has not changed since October 1, 2014; limitation of the freedom of movement for IDPs; limited practice ability of granting the right for the easy terms of studying at University (may be met by additional grants, charge-free rooms at the dormitory, free books and manuals, free Internet access etc.);the collection of legal charge for filing a lawsuit in court seeking protection of the rights of IDPs; service troubles of Single IDP Data Base. The issues of the lack of money for living, employment, provision of medical and psychological aid, the lack of selection criteria for the provision of IDPs with social services depending on their welfare, social status etc. are also pressing.